Generalized hyperkeratosis with sparing of palms and soles. - Albela, H.; Oh, H.H. (European Journal of Pediatric Dermatology, 2023)
We report a 12 year old girl with generalized hyperkeratosis and verrucous scales on her entire body, except her palms and soles. Genetic study revealed mutation in keratin 10, consistent with epidermolytic ichthyosis.